APPLICATION OF POETRY MUSICALIZATION LEARNING MEDIA AS AN EFFORT TO IMPROVE POETRY APPRECIATION ABILITY OF CLASS X STUDENTS - Annisa Nur Safitri; Sitti Rabiah; Nurmiah Muin (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine the increase in appreciation and learning outcomes of Indonesian language students in class X SMA Negeri 1 takalar. This research is a class action research carried out in cycles. The subjects in the study were 35 students of class X SMA Negeri 1 Takalar, consisting of 22 female students and 13 male students. Based on the observations made in cycle I and cycle II, the activities shown by students from the activities carried out in cycle I to cycle II showed a different attitude. After the action was taken in cycle II students became more active in learning, students were not only silent as in cycle I but students also followed the researcher's instructions, but also showed enthusiasm and interest in the learning process. The results of student test scores during the pre-cycle activities of students who achieved KKM were 7 students or by 10%, in cycle I activities students who achieved KKM were 12 people or by 30%, in cycle II students who achieved KKM were 30 people or by 89%. So it can be concluded that the effect of implementing poetry musicalization was successful because almost 35 students in class X SMA Negeri Takalar achieved KKM scores